Efl Reading Fluency: A Review Bibliometric And Vosviewer Analysis - Bahrum, Acep (Saba Jaya Publisher, 2023)
The study's objective is to present a review of reading fluency under the heading Reading Fluency.The Google Scholar database and published software were used to find the articles. 1,753 articles from 2013 to 2022 were examined. Using VOSviewer software, we have evaluated this database and made an effort to categorize the articles. There are four clusters. Ten items made up Cluster 1 (disability, basically students, fluency intervention, impact, intervention, reader, reading fluency, reaped reading, student, and teacher), seven items made up Cluster 2 (child, effect, fluency, language, present study, reading, and word), five items made up Cluster 3 (comprehension, oral reading fluency, relationship, research, and vocabulary), and four items made up Cluster 4 (accuracy, development, relation, and study). I am sure that through this way of reviewing reading fluency, students will be more active and reflective, gaining some knowledge and engaging their perceptions.